Power Generation from an Elastic Leidenfrost Hydrogel Piston Enabled Heat Engine. (November 2021) - Wang, Kun; Zhang, Haiqing; Wang, Yutao; Wang, Hongchen; Tan, Jie; Sun, Mingyang; Xu, Minyi; Chen, Guijun; Jiang, Dongyue; Liu, Xueling
Highlights: An elastic Leidenfrost heat engine with usable output power is presented. A maximum efficiency of 3.3% was achieved. The presented HP-TENG broadens the application field of Leidenfrost effect. Abstract: Leidenfrost phenomenon has been observed since 1756. Diverse Leidenfrost phenomenon based heat engines were developed for converting the thermal energy into mechanical form. Limited to the weak force, the Leidenfrost heat engines are rarely reported with usable electric power output. Here we propose an elastic Leidenfrost heat engine based power generator for the demonstration of thermal-to-electric power conversion. A saturated sodium polyacrylate super absorbing polymer sphere is employed as hydrogel piston for harvesting thermal energy to trigger elastic deformation and mechanical bouncing. A lightweight contact separation mode triboelectric nanogenerator (TENG) plays a role for the conversion from the tiny mechanical input into usable electric power. The dynamics of the hydrogel piston on hot plates, force generation during bouncing and electric power output are measured experimentally. The effects of piston stroke, working temperature, and water absorption rate of the hydrogel piston are discussed. A maximum open-circuit voltage of 22 V and peak power of 280 μW was obtained by a single 2-gram hydrogel piston and the output electric power from the hydrogel piston based power generator successfully lights up 22 commercial LEDs.